2021
DOI: 10.1371/journal.pone.0248811
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects of social media on the Saudi society during the Coronavirus Disease 2019 pandemic: A cross-sectional study

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has been posing a substantial challenge to human survival and well-being, which rely on the actions and behaviors of individuals. It is essential that accurate information is distributed; however, misinformation has been spread via social media. Consequently, the resulting panic has to be addressed while putting essential public health measures in place. It is also important to explore the link between the social media exposure and well-being. Therefore, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 66 publications
5
41
0
2
Order By: Relevance
“…For example, increased exposure to social media about the coronavirus was positively associated with the prevalence of anxiety, depression, and a combination of both, as verified in an online survey in China ( Gao et al, 2020 ). Similar relations between psychological distress and information consumption or social media use were found in other countries as well ( Bazán et al, 2020 ; Hammad and Alqarni, 2021 ; Mongkhon et al, 2021 ; Piltch-Loeb et al, 2021 ). The changes in the emotional state of health care professionals due to the valence of news about the coronavirus were evaluated just after they listened to audios with positive or negative content.…”
Section: Introductionsupporting
confidence: 79%
“…For example, increased exposure to social media about the coronavirus was positively associated with the prevalence of anxiety, depression, and a combination of both, as verified in an online survey in China ( Gao et al, 2020 ). Similar relations between psychological distress and information consumption or social media use were found in other countries as well ( Bazán et al, 2020 ; Hammad and Alqarni, 2021 ; Mongkhon et al, 2021 ; Piltch-Loeb et al, 2021 ). The changes in the emotional state of health care professionals due to the valence of news about the coronavirus were evaluated just after they listened to audios with positive or negative content.…”
Section: Introductionsupporting
confidence: 79%
“…There was one study within the reviewed literature that assessed the impact of information uncertainty on acute stress disorder ( Lin et al., 2020a ), finding a significant association. Research has indicated that exposure to misinformation via social media also has an association with anxiety, depression, and social isolation in the general population ( Hammad and Alqarni, 2021 ). With misinformation most likely to be shared across social media platforms and instant messaging services, resulting in greater misinformation exposure for younger age groups ( Lee et al., 2020 ), it is important for the role of information uncertainty and its impact on youth mental health to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Internet is a double-edged sword: Research has noted the negative impacts of digital technology on children, including poor self-esteem, mental health problems, and social difficulties (Wood et al, 2016 ). The use of social media, such as Instagram and YouTube, is also one of the leading causes of self-harm (McDool et al, 2016 ), cyberbullying, poor body image, and decreased academic performance (Wallsten, 2013 ; Akram and Kumar, 2017 ). Excessive use of social media generates anxiety (Sagioglou and Greitemeyer, 2014 ), addiction (Van Rooij and Prause, 2014 ), and can affect sleep behavior (Hisler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%